2018
DOI: 10.1155/2018/9640397
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic Empyema as Rare Complication of an Appendicular Mass: A Case Study and Review of the Literature

Abstract: Introduction Thoracic empyema is an infrequent complication of appendicitis that has rarely been reported in the literature. Case Presentation and Review of the Literature The case of a 11-year-old boy who was admitted for medical management of an appendicular mass is presented. His clinical course was complicated by the development of an appendicular abscess and an extensive right-sided empyema. A comprehensive review of the literature was conducted including the most representative cases. The data were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 20 publications
(25 reference statements)
0
9
0
Order By: Relevance
“…In a study conducted by Vasquez-Rios et al , it was found that about 19% of appendicular masses develop thoracic empyema following conservative management for the same. [ 6 7 ] Pregnancy can also be a risk factor for empyema formation following acute appendicitis. [ 7 8 ] In the case discussed herein, the patient did not have any features of appendicular mass at the time of presentation, making it difficult to suspect an empyema.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study conducted by Vasquez-Rios et al , it was found that about 19% of appendicular masses develop thoracic empyema following conservative management for the same. [ 6 7 ] Pregnancy can also be a risk factor for empyema formation following acute appendicitis. [ 7 8 ] In the case discussed herein, the patient did not have any features of appendicular mass at the time of presentation, making it difficult to suspect an empyema.…”
Section: Discussionmentioning
confidence: 99%
“…also showed that 25% of the patients with appendicitis were complicated at presentation. [ 5 6 ] There have been published reports on unilateral pleural empyema secondary to acute appendicitis, but the patient discussed herein had simultaneously complicated appendicitis and bilateral pyothorax.…”
Section: Introductionmentioning
confidence: 99%
“…Where described, patients usually have fever, nausea and abdominal pain in the right upper quadrant mimicking cholecystitis or liver abscess [ 2 ] . Much less common are patients with empyema, secondary to acute or postoperative appendicitis [ 3 ] . This phenomenon is explained by passage of bacteria from the abdomen to the thorax due to the pressure gradient, or the spread of infected fluids by the unilateral lymphatic flow across the diaphragm [ 3 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Pleural empyema secondary to abdominal infection is uncommon (1%–2% of all causes),1 and the majority of cases reported are secondary to intra-abdominal infections, mainly acute appendicitis 2. To a lesser extent, retroperitoneal infections, such as perinephric abscess3 4 or retrocecal appendicitis,5 may also present with pleural empyema, but it has not been described as a complication in cases of retroperitoneal diverticulitis or intestinal perforation in this cavity.…”
Section: Introductionmentioning
confidence: 99%